2012
DOI: 10.4304/tpls.2.12.2500-2507
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using Task-based Writing on EFL Learners’ Writing Performance and Creativity

Abstract: Abstract-This study investigated the impact of task-based writing on EFL learners' writing performance and creativity. For this purpose, 56 female intermediate Iranian EFL learners were chosen from a total number of 89 through their performance on a sample piloted PET. Based on the result, the students were randomly assigned to one control and one experimental group with 28 participants in each. Prior to the treatment, students took part in a writing test (part of PET) and the Abedi-Schumacher Creativity Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…Writing is a cognitive and dynamic process and cannot be memorized like the other static bodies of knowledge (Goddard & Sendi, 2008;Rao & Prasad, 2009, as cited in Marashi & Dadari, 2012). Perhaps one striking challenge is that many students consider writing as an assignment they are required to do for school, as "opposed to textual expression they engage in their own time" (Purcell, Buchanan, & Friedrich, 2013, p. 14).…”
Section: Introductionmentioning
confidence: 99%
“…Writing is a cognitive and dynamic process and cannot be memorized like the other static bodies of knowledge (Goddard & Sendi, 2008;Rao & Prasad, 2009, as cited in Marashi & Dadari, 2012). Perhaps one striking challenge is that many students consider writing as an assignment they are required to do for school, as "opposed to textual expression they engage in their own time" (Purcell, Buchanan, & Friedrich, 2013, p. 14).…”
Section: Introductionmentioning
confidence: 99%
“…That's why the Pakistani EFL learners of intermediate level face problems when they have to do creative writing either in the classroom or in the examination hall. In this regard, Marashi & Dadari (2012) maintain that task-based writing exercises a positive impact on the ESL learners' writing performance and creativity. The present study has also found out that 83% respondents claim that they do not learn lexical appropriateness while going through their textbooks.…”
Section: Resultsmentioning
confidence: 99%
“…From the survey, 67.5 % agreed TBLT improves learners' interaction skill. On the other way of research, Marashi and Dadari [26] had conducted an experimental research on the impact of using task-base writing on EFL learners' writing performance and creativity. The participants of the study were 56 Tehran's private language school.…”
Section: Review Of Tblt On Writingmentioning
confidence: 99%